Politik Hukum Pengalokasian Program Padat Karya Dengan Menggunakan Anggaran Pendapatan dan Belanja Daerah di Kota Surabaya - Ovi Shinta Mayasari (CV. Era Digital Nusantara, 2023)
Abstract: The Covid-2019 pandemic has caused Surabaya's economy to experience a slowdown in growth. The poverty rate for the City of Surabaya increased from the previous year in 2020 of 5.02%, increasing to 5.23% or 152,489 poor people in the City of Surabaya (2021) with 314,837 families registered as MBR. One of the programs in the city of Surabaya in facilitating the poor and unemployed to be competitive and independent in improving their welfare is to establish a Work-Intensive Program designed to involve Low-Income Communities (MBR) in managing assets owned by the Surabaya City Government. Purpose: This study aims to provide views and legal accountability in optimizing the implementation of the 2023 Surabaya City Revenue and Expenditure Budget (APBD) through the Padat Karya Program in alleviating poverty and reducing the open unemployment rate in the City of Surabaya. Design/Methodology/Approach: Research methods uses normative juridical research methods based on juridical aspects such as: norms, laws and regulations, and legal theories related to the authority to allocate the education budget obtained from scientific works, books, online media, and so on related to the object the research studied. Findings: Problems arise because development issues or problems in the City of Surabaya are in addition to continuing to handle and recover the economic and social impacts due to the Covid-19 Pandemic, the problem of the City of Surabaya is that the fulfillment of employment opportunities and employment has not been optimal in reducing unemployment and poverty rates exists so that a local government policy is needed by establishing the Labor Intensive Program using APBD funds. Originality/Value: This research attempts to discuss the legal reasons for the Surabaya City Government in allocating the Padat Karya program using APBD funds in the City of Surabaya as well as the legal responsibility for the Surabaya City government for allocating the Padat Karya program using APBD funds in the City of Surabaya based on Government Regulation Number 12 of 2019.